1997
DOI: 10.1161/01.cir.96.5.1381
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cholesterol Regulates Soluble Cell Adhesion Molecule Expression in Familial Hypercholesterolemia

Abstract: In the absence of changes in clinical chemical parameters, tumor necrosis factor-alpha, interleukin-6, and acute-phase reactant proteins, these results confirm in a clinical setting the upregulation of endothelial adhesiveness observed in experimental hypercholesterolemia and suggest a direct role for cholesterol in regulating this phenomenon, at least in familial hypercholesterolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 16 publications
7
62
1
1
Order By: Relevance
“…LDL-apheresis, consistent with previous reports, induced a reduction of circulating TC, LDL-C, apoB, HDL-C, and apoA-I ( 11,24 ). Two days after the procedure, all lipid parameters but HDL-C and apoA-I were still low; SR-BIand AD-mediated CEC were signifi cantly reduced immediately after LDL-apheresis and, in parallel with HDL-C and apoA-I plasma levels, returned to pretreatment values after two days ( Figs.…”
Section: Patient Serum Macrophage Clc Before Immediately After and supporting
confidence: 92%
“…LDL-apheresis, consistent with previous reports, induced a reduction of circulating TC, LDL-C, apoB, HDL-C, and apoA-I ( 11,24 ). Two days after the procedure, all lipid parameters but HDL-C and apoA-I were still low; SR-BIand AD-mediated CEC were signifi cantly reduced immediately after LDL-apheresis and, in parallel with HDL-C and apoA-I plasma levels, returned to pretreatment values after two days ( Figs.…”
Section: Patient Serum Macrophage Clc Before Immediately After and supporting
confidence: 92%
“…In addition, lipid apheresis in patients with familial hypercholesterolemia has been associated with concomitant decreases in circulating adhesion molecule levels. 32 Although small clinical studies 10,33 have suggested that increased levels of adhesion molecules are found in patients with dyslipidemia, a recent report from a large cohort of patients derived from the Atherosclerosis Risk in Communities study failed to demonstrate any significant association between sICAM-1 with triglycerides, total cholesterol, LDL-C, and HDL-C levels. 11 The significant associations between sICAM-1 with triglycerides and HDL-C levels observed in our study, however, support the concept that lipid metabolism may play a role in the modulation of cellular adhesion molecules.…”
Section: Rohde Et Al Sicam-1 and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Low-density lipoprotein (LDL) apheresis is a potentially useful treatment for conventional therapy-resistant hypercholesterolemic patients with coronary artery disease and PAD. 1,2 Previously, it was shown that a single LDL apheresis session enhanced the peripheral microcirculation, probably by increasing the production of nitric oxide (NO) and bradykinin, 3 reducing blood viscosity and adhesion molecules, 4 and inducing endothelium-dependent vasodilatation. 5 However, the precise molecular mechanism of the long-term effects of LDL apheresis on the improvement of the peripheral circulation remains unclear and warrants further investigation.…”
mentioning
confidence: 99%